2019
DOI: 10.5120/ijca2019919443
|View full text |Cite
|
Sign up to set email alerts
|

Forensic WhatsApp based Android using National Institute of Standard Technology (NIST) Method

Abstract: WhatsApp Messenger is a popular Instant Messaging (IM) application that is widely used in the 2017-2019 range. A large number of WhatsApp Messenger users will certainly have a positive and negative impact, the negative effects that are usually found are cases of crimes such as fraud into cybercrime crimes. The way to prove the perpetrators of the crime is to find evidence through digital forensics. This case will be revealed by one branch of digital forensics, namely mobile forensics because the evidence obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…indicate that the evidence was obtained through backup without rooting the device, and it was stored in another storage unit, and the analysis was started by open-source forensic tools, and the results showed that part of the conversations was encrypted and there were challenges in showing the results. It is not encrypted and the deleted conversations did not appear in the results, and the results indicate that to recover the deleted conversation, the device must be rooted [23]. indicates that a backup copy of Android was obtained and saved on an external memory card and analyzed on the open-source forensic analysis tools and that the database of correspondence and conversations was obtained, and even if the results obtained from Android are encrypted, the elements are evidence of correspondence, and here this study indicates that the device has not been rooted [24].…”
Section: Related Workmentioning
confidence: 93%
“…indicate that the evidence was obtained through backup without rooting the device, and it was stored in another storage unit, and the analysis was started by open-source forensic tools, and the results showed that part of the conversations was encrypted and there were challenges in showing the results. It is not encrypted and the deleted conversations did not appear in the results, and the results indicate that to recover the deleted conversation, the device must be rooted [23]. indicates that a backup copy of Android was obtained and saved on an external memory card and analyzed on the open-source forensic analysis tools and that the database of correspondence and conversations was obtained, and even if the results obtained from Android are encrypted, the elements are evidence of correspondence, and here this study indicates that the device has not been rooted [24].…”
Section: Related Workmentioning
confidence: 93%
“…This journal examines whether existing forensic tools can provide digital evidence to provide additional support and correlation to traditional investigative methods. This primarily focuses on artifacts from popular applications around the world (Iqbal & Riadi, 2019).…”
Section: Introductionmentioning
confidence: 99%